2016
DOI: 10.1007/s00280-016-3068-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, safety, and efficacy of lenalidomide plus dexamethasone in patients with multiple myeloma and renal impairment

Abstract: In patients with stable renal function, the recommended dose adjustments achieved proper plasma exposure and similar safety and efficacy across renal groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…The lenalidomide starting dose followed the dosing guidelines derived in that study [30]: 25 mg once daily for normal renal function and mild RI, 10 mg once daily for moderate RI, 15 mg once every other day for severe RI, and 5 mg once daily for ESRD. The study showed a highly significant linear relationship between lenalidomide clearance and CrCl in patients with MM [46]. This relationship was almost identical to that observed in patients with RI due to non-malignant conditions (Fig.…”
Section: Pharmacokinetics In Special Populationssupporting
confidence: 64%
See 3 more Smart Citations
“…The lenalidomide starting dose followed the dosing guidelines derived in that study [30]: 25 mg once daily for normal renal function and mild RI, 10 mg once daily for moderate RI, 15 mg once every other day for severe RI, and 5 mg once daily for ESRD. The study showed a highly significant linear relationship between lenalidomide clearance and CrCl in patients with MM [46]. This relationship was almost identical to that observed in patients with RI due to non-malignant conditions (Fig.…”
Section: Pharmacokinetics In Special Populationssupporting
confidence: 64%
“…To further assess whether the condition of MM may affect lenalidomide exposure, a phase II study was prospectively conducted and validated lenalidomide dose adjustments by evaluating the pharmacokinetics, safety, and efficacy of lenalidomide given with dexamethasone 40 mg weekly in patients with MM and various degrees of stable RI [46]. The study enrolled 38 patients (median age 65 years) with symptomatic MM.…”
Section: Pharmacokinetics In Special Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, it is controversy and debatable whether lenalidomide can be used to control solid tumors (14,16), although lenalidomide significantly inhibited growth of the chronic lymphocytic leukemia cells (19). In the present study, we further confirmed that lenalidomide alone had only a minimal effect on MDA-MB-231 cell viability, even at a very high dose of 320 µM, far beyond the clinically achievable concentration in humans (20). Thus, it is suggested that lenalidomide alone does not have much anti-proliferative activity in solid tumors, especially in TNBC cells.…”
Section: Discussionsupporting
confidence: 74%